Increase in prescription opioid use during pregnancy among Medicaid-enrolled women - Desai, Rishi J; Hernandez-Diaz, Sonia; Bateman, Brian T; Huybrechts, Krista F (Obstetrics and gynecology (New York. 1953), 2014)
To report the prevalence of prescription opioid use and evaluate the trends in a large cohort of Medicaid-enrolled pregnant women. A cohort of pregnancies was identified using data from the Medicaid Analytical eXtract for the period of 2000-2007. Dispensing of opioids, as a class and separately for individual agents, was evaluated using claims from filled prescriptions. Variations in patterns of prescription opioid fills were examined by demographic characteristics, by geographic region, and over time. Median number of opioid prescriptions dispensed and cumulative days of availability for prescription opioids during pregnancy were reported. The study population consisted of more than 1.1 million women with completed pregnancies from 46 U.S. states and Washington, DC. One of five women from our cohort (21.6%) filled a prescription for an opioid during pregnancy; this proportion increased from 18.5% in 2000 to 22.8% in 2007. Substantial regional variation was seen with the proportion of women who filled a prescription during pregnancy, ranging between 9.5% and 41.6% across the states. Codeine and hydrocodone were the most commonly prescribed opioids. Among women filling at least one opioid prescription, the median (interquartile range) number of prescriptions filled was 1 (1-2) and the median (interquartile range) cumulative days of opioid availability during pregnancy were 5 (3-13) days. We observed high and increasing number of filled prescriptions for opioids during pregnancy among Medicaid-enrolled women. These findings call for further safety evaluations of these drugs and their effects on the developing fetus to inform clinical practice. II.